(untitled) (Archive of Conferences, 2021)
In the Uzbek literature of the early twentieth century, especially in poetry and prose, ideological, semantic, artistic and methodological changes and innovations are observed. The emergence of Uzbek novels and dramaturgy, the emergence and development of the Uzbek press also coincide with this period. As a result of the spread of Jadid ideas in Turkestan, changes took place in all spheres of society. Especially in literature, the theme and idea, form and style, developed in a new stream of poetic features. The creative activity of Abdulhamid Sulaymon oglu Cholpon, one of the prominent representatives of Jadidism in this period, is of special importance